Lipid Deposition in Skeletal Muscle Tissues and Its Correlation with Intra-Abdominal Fat: A Pilot Investigation in Type 2 Diabetes Mellitus - Manoj Kumar Sarma; Andres Saucedo; Suresh Anand Sadananthan; Christine Hema Darwin; Ely Richard Felker; Steve Raman; S. Sendhil Velan; Michael Albert Thomas (Metabolites)
Background/Objectives: This study evaluated metabolites and lipid composition in the calf muscles of Type 2 diabetes mellitus (T2DM) patients and age-matched healthy controls using multi-dimensional MR spectroscopic imaging. We also explored the association between muscle metabolites, lipids, and intra-abdominal fat in T2DM. Methods: Participants included 12 T2DM patients (60.3 ± 8.6 years), 9 age-matched healthy controls (AMHC) (60.9 ± 7.8 years), and 10 young healthy controls (YHC) (28.3 ± 1.8 years). We acquired the 2D MR spectra of calf muscles using an enhanced accelerated 5D echo-planar correlated spectroscopic imaging (EP-COSI) technique and abdominal MRI with breath-hold 6-point Dixon sequence. Results: In YHC, choline levels were lower in the gastrocnemius (GAS) and soleus (SOL) muscles but higher in the tibialis anterior (TA) compared to AMHC. YHC also showed a higher unsaturation index (U.I.) of extramyocellular lipids (EMCL) in TA, intramyocellular lipids (IMCL) in GAS, carnosine in SOL, and taurine and creatine in TA. T2DM patients exhibited higher choline in TA and myo-inositol in SOL than AMHC, while triglyceride fat (TGFR2) levels in TA were lower. Correlation analyses indicated associations between IMCL U.I. and various metabolites in muscles with liver, pancreas, and abdominal fat estimates in T2DM. Conclusions: This study highlights distinct muscle metabolite and lipid composition patterns across YHC, AMHC, and T2DM subjects. Associations between IMCL U.I. and abdominal fat depots underscore the interplay between muscle metabolism and adiposity in T2DM. These findings provide new insights into metabolic changes in T2DM and emphasize the utility of advanced MR spectroscopic imaging in characterizing muscle-lipid interactions.